Postawa "homo ethicus" jako ideał etyczny w koncepcji filozoficznej Henryka Elzenberga - Zegzuła-Nowak, Joanna (Annales. Etyka w Życiu Gospodarczym, 2009)
The main purpose of this article is a presentation of the H. Elzenberg's philosophical theory of the ethical ideal. I pay special attention to the most interesting, from the ethical point of view, parts of his concept. Elzen-berg proposed the ethical ideal, the so called ‘homo ethicus’. I present two ways of its realisation: melioristic and soteristic. My aim is also to prove that Elzenberg’s theory demonstrates that some features of ethical activity distinguish a human being from the background of the natural world and make them exceptional. These attributes include: the realisation of the perfect values such as the good and the beauty, having an ethical will, self-sacrifice, aspiring to perfection and moral salvation.